Pengaruh Kualitas Produk, Kualitas Layanan, Dan Social Media Marketing Terhadap Keputusan Pembelian Di PT Multi Prestasi Mas - Bayhaqi, Dejan Nouval; Silitonga, Parlagutan (Fakultas Ekonomi Universitas Tjut Nyak Dhien Medan, 2025)
Purpose – This study aims to determine the relationship between product quality, service quality, and social media marketing on purchasing decisions at PT. Multi Prestasi Mas. Novelty – Most previous studies have focused solely on the direct influence of product quality and service quality on purchasing decisions, without considering the role of social media marketing as a modern marketing platform. In this study, social media marketing is positioned as a strategic tool in promoting and creating interaction with customers. Method – The population in this study consisted of customers of PT. Multi Prestasi Mas. A total of 100 respondents were selected using purposive sampling based on relevant criteria. Data were collected through a questionnaire and analyzed using multiple linear regression with the help of SPSS version 25. Findings – The results indicate that product quality, service quality, and social media marketing have a significant influence, both partially and simultaneously, on purchasing decisions at PT. Multi Prestasi Mas. Limitations and Implications – This study is limited to the skincare and cosmetics manufacturing sector, thus its findings may not be widely generalizable to other service sectors or the manufacturing industry in general. The contribution of this research provides a useful reference for practitioners, especially business actors in the beauty and cosmetics industry, in designing marketing strategies that optimize product quality, service quality, and social media marketing to enhance purchasing decisions.